2019
DOI: 10.14513/actatechjaur.v12.n2.501
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Axlebox Accelerations in Correlation with Track Geometry Irregularities

Abstract: Stochastic track irregularities influence additional dynamic forces developed in the vehicle-track interaction that lead to faster deterioration of track. For economical track maintenance it is important to understand the relationship between the irregularities recorded by conventional track geometry measuring car and the resulting dynamic vehicle responses. This paper focuses on the correlation between lateral and vertical axlebox accelerations and differently processed track geometry parameters based on a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…There is other plan to compose FEM models to be able to simulate longer railway track sections with different support characteristics. The results from the longer railway tracks' FEM model are able to be set against the field tests [39] [40] [41] [44].…”
Section: Discussionmentioning
confidence: 99%
“…There is other plan to compose FEM models to be able to simulate longer railway track sections with different support characteristics. The results from the longer railway tracks' FEM model are able to be set against the field tests [39] [40] [41] [44].…”
Section: Discussionmentioning
confidence: 99%
“…Several types of mathematical functions have been previously considered, such as splines, polynomials from the 3 rd to 7 th degree, and others. For example, an exponential function with a complex basis was used in [24] precisely to reproduce the track profile in line with the results of measurements by a machine with an asymmetric chord, but for the task of establishing a correlation between accelerations and track geometry.…”
Section: The Function Of Processing Negative Values Of An Arraymentioning
confidence: 99%
“…Additional parameters such as vehicle velocity, GPS location and track defect images were monitored. An experimental investigation of the relationship between the irregularities recorded by a conventional track-geometry-measuring car and the resulting dynamic vehicle responses of axle-box accelerometer is presented in the paper [ 27 ]. It was concluded that the differences of the vertical axle-box accelerations and the lateral axle-box acceleration are practicably proportional.…”
Section: Introductionmentioning
confidence: 99%